Shola: a 3D porous hydrophobic-oleophilic lignocellulosic material for efficient oil/water separation - Mondal, Keya; Advani, Kushagra; Ghosh, Snigdha; Shanmugnathan, Kadhiravan; Kulsi, Goutam; Sivaram, Swaminathan; Sen Gupta, Sayam (Journal of Materials Chemistry A, 2025)
Transitioning from the fossil fuel era to a sustainable future requires increasing adoption of high-performing renewable materials in industrial applications. Natural polymers derived from lignocellulosic materials are often considered more environmentally friendly than their petroleum-based synthetic analogs. Aeschynomene aspera, commonly known as Shola, has been found to be a large source of amorphous cellulose and a useful sorbent for the removal of oil from water. The Shola pith, the pure white inner stem, is rich in cellulose and has an exquisite three-dimensional and hierarchical porous architecture created by nature. The pith consists of about 70 wt% cellulose as the main chemical component, which is much higher than what is found in other lignocellulosic sources. In addition, the pith has about 12 wt% hemicellulose, 2-3 wt% pectin, 10 wt% lignin, 2.5 wt% wax, and 2 wt% protein as other chemical components. It was observed that water has a high contact angle (135 degrees) on the surface of the pith, while oil droplets instantly spread on the surface, indicating excellent hydrophobic-oleophilic properties. Further studies reveal that the Shola pith exhibits a fast and high sorption capacity of 40-60 g/g for various oils and organic liquids. Silicone oil shows a sorption capacity of about 166 g/g. When applied to oil-floating-over-water, the Shola pith exhibits high selectivity for oil over water; almost all oil on the surface could be removed, leaving no trace of oil on the water surface. The Shola pith can also efficiently separate oil from an oil-in-water emulsion. This behavior is unprecedented in natural sorbents. The used material sorbs a considerable volume of the oil even after the 7th cycle. Furthermore about 95% of sorbed oil could be recovered from the material by solvent extraction. This study reveals for the first time some of the unique and interesting properties of Shola, a widely found biomass native to the eastern parts of the Indian subcontinent, and opens up possibilities of exploiting it for valuable applications.